Analisis Pola Spasial dan Determinan Kemiskinan di Provinsi Sumatera Selatan - Nazipawati Nazipawati; Tri Mulyaningsih (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of this study was to determine the spatial pattern of the poverty rate and to determine the factors that may have a spatial influence on the poverty rate in South Sumatra Province. The factors that are suspected to influence and have a spatial (regional) dependency effect on the poverty rate are economic growth, population, length of roads in good condition, number of households that have access to decent drinking water, number of villages that can receive internet signals and Gross Regional Domestic Product per capita 2021 year in 15 districts/cities. The data used in this study were sourced from the South Sumatra Central Bureau of Statistics and spatial identity data sourced from https://gadm.org/download_country_v3.html. The analysis method used is spatial regression analysis using the Stata 17 application. The results of this study show that based on the map there are groupings or clusters of poverty rates. However, there is no spatial dependency effect on the poverty rate in South Sumatra Province. Economic growth has a negative but insignificant effect on the poverty rate, population has a negative and significant effect on the poverty rate, the length of highways in good condition has a positive but insignificant effect on the poverty rate, the number of households with access to safe drinking water has a negative but insignificant effect on the poverty rate, the number of villages that can receive internet signals has a positive and significant effect on the poverty rate, and GRDP per capita has a positive and significant effect on the poverty rate in South Sumatra Province.